Detection of Multidrug Resistance in Salmonella sp. Isolated from Diarrhoea of Bovine Calves in Mhow, Indore - Sikrodia, Ravi; Chhabra, Daljeet; Supriya, Shukla; Audarya, S. D.; Jogi, Joycee; Gangil, Rakhi; Sharda, Rakesh; Jatav, G. P. (International Journal of Bio-resource and Stress Management, 2026)
The research was conducted during July, 2021 to April, 2022 in the Department of Veterinary Microbiology, Veterinary College, Mhow, Madhya Pradesh, India, with the objective of multidrug resistance in Salmonella sp. isolated from diarrhoea of bovine calves in Mhow, Indore, India. A total of 250 faecal samples were collected from diarrheic bovine calves and transported to the laboratory for immediate processing. The fecal sample was inoculated in buffered peptone water (BPW) as a pre-enrichment and incubated at 37ºC for 16 hrs. After 16 hrs. Rappaport Vassiliadis (RV) broth were inoculated from this BPW with the help of inoculation loop and again incubated at 37°C for 18 hrs. followed by culture on MacConkey agar, XLD agar and BG agar. On MacConkey agar Salmonella shows colorless colony. Typical colonies of Salmonella grown on XLD-agar has a slightly transparent zone of reddish color and a black center. While on the BG agar colonies of the Salmonella showing pinkish white in color. Twenty-three Salmonella isolates were initially identified phenotypically and further confirmed by PCR targeting the invA gene. Antimicrobial susceptibility testing was conducted using 15 antibiotics. The isolates showed the highest sensitivity to co-trimoxazole, while the highest resistance was observed against enrofloxacin. Molecular analysis of six antibiotic resistance genes revealed that the sul1 gene was the most prevalent among the isolates, followed by blaCTX-M, blaSHV, aadA and blaTEM. The tetA gene was not detected in any of the isolates. Additionally, hemolysis testing indicated that none of the Salmonella isolates exhibited hemolytic activity on blood agar.